Demographic Dynamics in Latin America (1961–2023): A Characterization using Functional Biplots and Neutrosophic TOPSIS Neutrosophic TOPSIS - Inés Alejandra Vicencio Pardo; José Luis Vicente Villardón (Neutrosophic Sets and Systems)
This study analyzes the Growth Rate behavior Demographic (TDC) of the countries Latin Americans during the period 1961–2023 through Methods Multivariate Functional and Neutrosophic TOPSIS. The techniques descriptive, grouping functional and display using Functional Biplot allowed identify curves of countries with behavior atypical (Venezuela, Uruguay, Honduras) and group countries with patterns similar in different points in the period studied. The integration of TOPSIS Neutrosophic modeled uncertainty in key factors such as policies internal, migration and access to family planning, classifying countries according to his performance demographic. The results reveal a decrease sustained TDC over 63 years in the region, with a variance explained by 87% Component Analysis Main Functional (FPCA), highlighting milestones as changes in policies internal and external and the effects of migration, framed in the context economic, political and social of each country.